Leukokoria sebagai Tanda Peringatan Penyakit Coats dan Gangguan Retina Lainnya: Tinjauan Pustaka - Paramita, Carennia; Yulia, Dian Estu (Cermin Dunia Kedokteran, 2025)
Coats’ disease is an idiopathic condition characterized by non-hereditary exudative retinopathy caused by abnormal retinal vascular development. Patients often present with signs such as leukocoria, significant vision loss, and strabismus. Some characteristic features include telangiectasia, aneurysms, and exudative retinal detachment. Ultrasonography and computed tomography scan can detect masses and calcifications, which are useful in ruling out differential diagnosis of retinoblastoma. Coats’ disease has 5 stages, but it is not uncommon for patients to seek treatment in advanced stages or when it has progressed to a malignancy in children, such as retinoblastoma, therefore the patient will be referred for enucleation.